2020
DOI: 10.3390/microorganisms8060927
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Toxoplasma gondii and Risk Factors Associated with the Infection in Stray Dogs and Cats of Panama

Abstract: Stray animals such as dogs and cats have an important role in maintaining the transmission cycles and dissemination of Toxoplasma gondii. Therefore, the objective of this study was to evaluate the frequency of T. gondii in stray dogs and cats in six different regions of Panama and determine risk factors associated with the dynamics of infection in each of the studied regions. Data were obtained using serological tests for the detection of anti-T. gondii IgG and IgM antibodies. The results of this study reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Considering that dogs and cats can be involved in the maintenance of the urban and periurban life cycle of T. gondii, and that they usually share the same areas within cities, serological surveys in both species are the key aspect to address control strategies of this zoonotic pathogen, especially in areas where there are colonies of free-roaming dogs and cats in close contact with humans (Fábrega et al, 2020;Park et al, 2020). In fact, this health concern is reflected in various studies of T. gondii seroprevalence in dogs and cats previously conducted in several areas around the world from a One Health perspective (Rengifo-Herrera et al, 2017;Cong et al, 2018;de Oliveira et al, 2019;Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that dogs and cats can be involved in the maintenance of the urban and periurban life cycle of T. gondii, and that they usually share the same areas within cities, serological surveys in both species are the key aspect to address control strategies of this zoonotic pathogen, especially in areas where there are colonies of free-roaming dogs and cats in close contact with humans (Fábrega et al, 2020;Park et al, 2020). In fact, this health concern is reflected in various studies of T. gondii seroprevalence in dogs and cats previously conducted in several areas around the world from a One Health perspective (Rengifo-Herrera et al, 2017;Cong et al, 2018;de Oliveira et al, 2019;Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, 32.5% of the samples from KL/Selangor were seropositive compared to those from Penang/Kedah (12.5%). The seroprevalence rates in most of the locations suggest that similar factors may be influencing the exposure of stray dogs to T. gondii infection [35]. Nevertheless, the location-KL/Selangor with highest seroprevalence is relatively more urbanized and densely populated, which may increase the exposure of stray dogs to environment contaminated with oocysts.…”
Section: Discussionmentioning
confidence: 93%
“…Saldanha-Elias et al [36] reported that stray dogs from urban areas had higher risk of T. gondii seropositivity compared to those from rural areas. Specific factors common in urban areas such as high population of cats, human-related activities leading to more garbage cans in the street, and exposure to poorly cooked meat may heighten the risk of T. gondii infection in stray dogs [35]. Additionally, shelters in the sampled areas with high seroprevalence might have cats that readily interact with the quarantined dogs or share a common environment.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic animals have been considered risk factors due to their constant interaction with humans [ 8 , 44 ]. Previous studies carried out in West Panama and in different regions of Panama province showed high frequencies of infection by T. gondii in dogs and cats, both strays and pets [ 45 , 46 ]. The bivariate analyses carried out in this study did not show significant association between the presence of domestic animals and the frequency of infection.…”
Section: Discussionmentioning
confidence: 99%